KUALITAS SISTEM INFORMASI UNTUK MENINGKATKAN EFEKTIVITAS LAYANAN PENGADUAN MASYARAKAT BERBASIS ONLINE DI DINAS KOMUNIKASI DAN INFORMATIKA KOTA BANDUNG PROVINSI JAWA BARAT - Teresa Irmina Nangameka (Jurnal Teknologi dan Komunikasi Pemerintahan, 2020)
This research focuses on describing and analyzing the effectiveness of the Online-Based Public Complaints Information System which been known LAPOR! from information system quality’s perspective in Bandung city. LAPOR! is a concrete step to integrate the management of public service complaints so that it requires all Ministries / Institutions and Local Governments to be involved in its management. The phenomenon of problems that occur in Bandung related to the application of LAPOR! are complaints channels of each agency that have not been integrated in LAPOR!, LAPOR!'s socialization which is still uneven, also there are reports of complaints that have not been resolved, and public perceptions about complaints online itself. The researcher used the information systems theory of DeLone and McLean (2013). Combining a qualitative theory with a descriptive approach and also using interview, observations and documents about LAPOR! conducted by the Agency of Communication and Information of Bandung city, these are how the researcher works. The results showed that the quality of information system of LAPOR! can increase the effectiveness of managing public service complaint. LAPOR! with its features and menu has been able to facilitate several community problems through the system. Some problems of information system that occur such as network, maintenance, and features availability, or technical errors still can be handled by internal experts in the agency. In terms of website interface of LAPOR!, the addition of graph report of complaint in website can improve its management. Keywords: LAPOR!, effectiveness, information systems